Studi Komparatif Komprehensif Sistem Ekonomi Islam, Kapitalis dan Sosialis - Abdurrahman (JURNAL ALAMIAH, 2022)
In the midst of the ongoing trend of Islamic economics, it is necessary to have an in-depth study of this system. Is it really just a rule of religious norms? Or just follow the spiritual trend that has recently been increasing. Actually the Islamic economic system is different from other economic systems, it is not the result of the adoption of a socialist system that fights for pseudo equal rights. It is also very different from the capitalist system which gives property rights to individuals freely. The Islamic economic system is a system that is based on divine values and is built on general principles for the implementation of all economic activities. The capitalist economic system is based on individual freedom to own various wealth that exists on this earth without any restrictions, this has an effect on the inequality of the social system, where the rich get richer and the poor get poorer. Apart from that, various social problems emerged, such as the existence of landlords and slaves. The end of this system was a rebellion of workers who demanded their rights as human beings. If the capitalist system protects the various interests of the bourgeoisie, then the socialist system fights for equal rights for all citizens. The equality they want is equality in all rights and eliminates ownership rights to a material object. In this case, each individual is not allowed to have material rights except for those that are the necessities of life. All economic systems are regulated by the State. This system gives the impression that they are defending the workers, but in essence this system is a protection for leaders and officials to exploit people's wealth. The Islamic economic system has methods and principles that are different from other economic systems, it gives ownership rights to an object, but there are standard rules so that wealth is not only among the rich. The mechanism used is the presence of zakat law. Some of the wealth that is needed by many people is managed by the state and may not be owned by individuals. This is where the Islamic economic system becomes a comprehensive economic system and will be suitable to be applied anytime and anywhere.